Body Mass Index And Age With Ankle Injury In Basketball Player - Wiranata, Philipus; Handoyo, Henry R; Kurniawan, Patricia M (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
Introduction: Ankle injuries occur when foot do some movements, such as twist or stretch the ankle. At certain point, this movement can cause ligament tears or dislocation. About 90 percent of all ankle injuries are sprain. Only 15 percent are ankle fracture. Ankle sprain is one type of ankle injury. Aim: The purpose of this research was to determine the relationship between Body Mass Index (BMI) and Age with Ankle Injury in Basketball Player. Methods: This research used cross sectional study method. The analysis used Spearman correlation test to evaluate the relationship of each variable. This observational analytic study started from 2017 August 1st until 2017 August 31st. The population of this study is 250 people. 145 of the 250 respondents are respondents who comply the criteria. Result: Showed weak relationship (r= 0.227) and significant (p=0.006) for BMI and ankle injury. While, for age and ankle injury the result was weak relationship (r=0.310) and significant (p=0,000). Conclusion: The conclusion of this research was the increasing of BMI and age results in high potential suffer from ankle injury.